Lebanon Education Public Expenditure Review 2017 - Abdul-Hamid, Husein; Sayed, Haneen Ismail; Krayem, Dima; Ghaleb, Joey R. (World Bank, Washington, DC, 2018)
This Education Public Expenditure Review (PER) analyzes public expenditures and outcomes since 2004. Its purpose is to help the Ministry of Education and Higher Education (MEHE) set priorities; and make decisions on resource allocation, utilization, efficiencies, and management, and in achieving learning goals against a backdrop of serious economic and political challenges. The influx of refugees since 2011 from the Syria Crisis has created new issues for MEHE, which compound pre-conflict challenges in the education sector. The PER uses multiple sources including administrative and household-level micro-survey data, as well as results of national and international assessments among others (see annex 1 for full sources and description). It tackles the composition of and trends in government spending and resulting impact on education inputs and outcomes, as well as internal and external efficiencies. The equity dimension—in terms of geographic location, household socioeconomic status, and gender—is also explored in detail. It evaluates current processes in budget planning and execution. Finally, the PER makes a series of policy recommendations for the government's consideration.